Using Fishermen’s Knowledge and GIS to Identify Fishing Grounds, Gears and Species in the Projected Marine Protected Area ‘Jabal Moussa’ - Derdabi, Mohamed Rida; Aksissou, Mustapha; Toujgani, Ihssane (Journal of Sustainability and Environmental Management, 2022)
Marine spatial planning and ecosystem based management such as MPA’s has been used as tools to manage human activities, to conserve coastal ecosystems and biodiversity for the sustainable use of oceans, seas and marine resources. In this study, we focused on establishing a spatial distribution of the fishing grounds used by local fishermen in the projected MPA “Jabal Moussa”, identifying the most important species targeted, the gears used, and the depths of fishing grounds. A survey with 99 skippers was conducted between February and March 2019. Then data collected was analyzed and geo-referenced through geographic information system (GIS). The results identified 16 fishing grounds. Distribution of fishing gears was dominated by the blackspot seabream longline which was the most used gear. The most targeted species was the blackspot seabream. Fishing grounds where blackspot seabream was found had a deep ranging from 95.9 m to 328.9 m. Results of the study will provide managers of the projected MPA with valuable information and data to help the to adopt direct measures that can reduce the pressure on these valuable species, preserve the ecosystem and lead to a sustainable fishing.